Pengaruh Profesionalisme Kerja dan Kompetensi Auditor, terhadap Kualitas Audit Inspektorat Provinsi Sulawesi Barat - Syamsul Bakhtiar Ass; Mustafa Mustafa; Hajar Hajar (Al-Buhuts, 2023)
Abstract This research was conducted to determine the effect of work professionalism and auditor competence on audit quality. using primary data through a questionnaire of 52 respondents, the determination of respondents using a purposive sampling technique consisting of auditors and Supervisors for the Implementation of Regional Government Affairs (PPUPD). Data were analyzed using the SPSS 25 program. The results showed that: (1) Work professionalism has a positive and significant effect on audit quality in the inspectorate of West Sulawesi Province; (2) Auditor competence has a positive and significant effect on audit quality at the inspectorate of West Sulawesi Province; (3) Work professionalism and auditor competence simultaneously have a positive and significant effect on audit quality in the inspectorate of West Sulawesi Province